A Systematic Review of Global Prospectives on Digital Agriculture and the Startup Ecosystem - Mishra, Nibedita; Nanda, Chinmaya; Kulkarni, Sutej Raghavendra (NG Agricultural Sciences, 2026)
Digital agriculture has shifted its focus on the limited scope of precision tools to the greater shift in agricultural production, advisory services, logistics, traceability, and governance. Meanwhile, entrepreneurial activities and start-ups have become significant anecdotes that can transform digital technologies into products, platforms, and services that provide a commercial business. Nevertheless, the existing body of literature connecting digital agriculture and start-up ecosystem is scattered across the body of technological literature, innovation studies, rural sociology, and agri-food management. This review paper is a synthesis of the recent peer-reviewed evidence on that intersection. With Scopus, the search query or query 1 was Digital agriculture AND Start-up and 76 records were obtained; query 2 was 2021-2026 and the document type was Journal article; query 3 was 23 studies were obtained and finally qualified as the final results. The qualitative thematic synthesis of included records was done based on titles, abstracts, and key-word fields followed by a PRISMA-based review design. The reviewed literature is summarized in five themes conceptual framings of digitalisation in agriculture; start-up-led innovation and entrepreneurial intermediation; digital technologies and precision systems; ecosystem support mechanisms and governance; and sustainability, adoption, and socio-economic consequences. Through all these themes, it is indicated that start-ups are the focus of experimentation, commercialization and reconfiguring value chains, yet their success is determined by institutional coordination, financial accessibility, platform governance, digital literacy, and alignment of technological solutions with the reality of farming. It is a rapidly growing field that is nonetheless still heterogeneous and uneven with a lack of comparative work and integration of agronomic, entrepreneurial, and policy views.